Capital Intensity, Aggregation, and Consumption Behavior - Bigman, David (Quarterly Journal of Economics, 1979)
I. The analytical framework, 691.—II. Capital intensity and aggregation, 695.—III. Regular consumption behavior, 700.—IV. Summary and conclusion, 703.